The construction of tie-back earth retaining structures / Muhammad Izham Irwan - Irwan, Muhammad Izham (Universiti Teknologi MARA, Perak, 2022)
Tie back earth retaining structure is a very important thing to elaborate, therefore this report will discuss about tie back earth retaining structure efficiency for the building envelope based on code of practice retaining structure efficiency. This report was conducted for the retaining structure at Alam Impian and Puncak Alam, Selangor. The objective of this report is to compare the capacity of two site and how far it fulfills the requirements in the guideline. It will focus on tieback earth retaining structure conservation that provides a comfortable environment for its occupants. To illustrate the function of retaining wall envelope as an important aspect to focus on wall surface design achievement and then to evaluate how far the potential of the wall involvement that could fulfill the soil pressure. This report will also look at the retaining structure management based on the guideline by producing the use of effective and continuous method and to evaluate the quality of retaining structure usage that gives a better impact for the infrastructure in the future.